2011
DOI: 10.1161/circresaha.111.245969
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Mesenchymal Stem Cells Mobilize cKit + and CD133 + Bone Marrow Progenitor Cells and Improve Regional Function in Hibernating Myocardium

Abstract: Rationale: Mesenchymal stem cells (MSCs) improve function after infarction, but their mechanism of action remains unclear, and the importance of reduced scar volume, cardiomyocyte proliferation, and perfusion is uncertain.Objective: The present study was conducted to test the hypothesis that MSCs mobilize bone marrow progenitor cells and improve function by stimulating myocyte proliferation in collateral-dependent hibernating myocardium. Methods and Results: Swine with chronic hibernating myocardium received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
91
4
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 67 publications
(81 reference statements)
13
91
4
1
Order By: Relevance
“…However, this notion has been challenged by several examples of transition from one cell type to another or, more unexpectedly, from one cell lineage to another lineage (67)(68)(69)(70). The unanticipated plasticity of adult HSCs to generate cells beyond their own tissue boundary became the driving force of a series of studies in which HSCs were implemented experimentally to restore the necrotic myocardium after infarction (71)(72)(73)(74)(75)(76)(77)(78).…”
Section: Hscsmentioning
confidence: 99%
“…However, this notion has been challenged by several examples of transition from one cell type to another or, more unexpectedly, from one cell lineage to another lineage (67)(68)(69)(70). The unanticipated plasticity of adult HSCs to generate cells beyond their own tissue boundary became the driving force of a series of studies in which HSCs were implemented experimentally to restore the necrotic myocardium after infarction (71)(72)(73)(74)(75)(76)(77)(78).…”
Section: Hscsmentioning
confidence: 99%
“…On the contrary, infusion of lower cell numbers did not hamper coronary flow in previous experiments. Valina et al 22 infused only 2 million MSCs directly after AMI, and Suzuki et al 23 infused 15 million MSCs per coronary artery in hibernating myocardium, both without any flow-related side-effects. Also, in a study by Johnston et al 24 , infusion of 10 million cardiosphere-derived cells (20 micrometer in diameter) after AMI was deemed safe, whereas 25 million cells or more caused significant infarctions.…”
Section: Previous Experience With Intracoronary Infusion Of Mscsmentioning
confidence: 99%
“…146 Although it has been shown that MSCs differentiate directly into cardiomyocytes, 26,34 the majority remain as MSCs and generate cell to cell interactions with host cardiomyocytes, stimulating endogenous cardiomyocyte turnover and CSC differentiation. 26,34,147 In addition to stimulating myocyte turnover and progenitor cell recruitment, 148 endogenous CSCs also promote repair through direct remuscularization 27 and these effects are enhanced by MSCs. Although some findings suggest that resident CSCs contribute only minimally to cardiac regeneration, 149 others have demonstrated that this is a variable process which is significantly enhanced after cell-cell contact with MSCs.…”
Section: Differentiationmentioning
confidence: 99%